The effectiveness of core stabilization and schroth exercise on pain reduction in adolescents with scoliosis - Fitratilla, Fitriani; Yani, Fitri; Setiawan, Danur; Laksono, Tri (Universitas 'Aisyiyah Yogyakarta, 2024)
Background: Disorders of the spine, such as scoliosis, kyposis, and lordosis, are often complained about by many people. Currently, disorders of the spine are not only limited to adults and the elderly. They can also affect children and adolescents, where the prevalence of adolescent idiopathic scoliosis in the world ranges from 0.47% to 5.2%. The spine has a crucial role in human movement activities, playing a role as a support and enforcer of the body. In this regard, appropriate intervention for people with scoliosis is very important to be carried out. Objective: To find out how effective core stabilization and schroth exercise are at reducing pain in scoliosis in adolescents aged 13-15 years. Research Method: The type of research used is quasi-experimental research with a pre-test and post test two-group design. Results: After 4 weeks of intervention with a frequency of two times a week, there was a significant reduction in scoliosis pain in adolescents. Both models of exercise core stabilization and schroth exercise – are equally effective. Suggestion: The researcher is expected to expand this research by increasing the number of samples and extending the duration of the study.